Mycotoxin exposure in rural residents in northern Nigeria: A pilot study using multiurinary biomarkers - Ezekiel, C.N.; Warth, B.; Ogara, I.M.; Abia, W.A.; Ezekiel, V.C.; Atehnkeng, J.; Sulyok, M.; Turner, P.; Tayo, G.; Krska, R.; Bandyopadhyay, Ranajit (Elsevier, 2014)
A pilot, cross-sectional, correlational study was conducted in eight rural communities in northern Nigeria toinvestigate mycotoxin exposures in 120 volunteers (19 children, 20 adolescents and 81 adults) using a modernLC–MS/MS based multi-biomarker approach. Firstmorning urine samples were analyzed and urinary biomarkerlevels correlated with mycotoxin levels in foods consumed the day before urine collection. A total of eightanalytes were detected in 61/120 (50.8%) of studied urine samples, with ochratoxin A, aflatoxin M1 andfumonisin B1 being the most frequently occurring biomarkers of exposure. These mycotoxin biomarkers werepresent in samples from all age categories, suggestive of chronic (lifetime) exposures. Rough estimates ofmycotoxin intake suggested some exposureswere higher than the tolerable daily intake. Overall, rural consumerpopulations fromNasarawaweremore exposed to severalmixtures ofmycotoxins in their diets relative to thosefromKaduna as shown by food and urine biomarker data. This study has shownthat mycotoxin co-exposuremaybe a major public health challenge in rural Nigeria; this calls for urgent intervention.